MTOR Inhibition Rejuvenates the Aging Gingival Fibroblasts through Alleviating Oxidative Stress. (19th July 2017) - Xia, Yiru; Sun, Mengjun; Xie, Yufeng; Shu, Rong
Abstract : The aging periodontium may be vulnerable to periodontal pathogens and poor response to inflammation and susceptible to tumorigenesis. Human gingival fibroblasts (hGFs) through continuously replicative culture served as an in vitro surrogate for aging. To investigate the effects of the mechanistic target of rapamycin (mTOR) inhibition on the aging gingiva, we stimulated the high-passage hGFs with rapamycin (20 nmol/L) for 3 days and 30 days. The cellular and biological changes were examined by immunofluorescence, real-time PCR, ELISA, Western blotting, and flow cytometry. The data demonstrated that the inhibition of mTOR signaling led to fewer senescence-associated beta-galactosidase- (SA- β -Gal-) positive cells, delayed the onset of senescence, preserved the capability of proliferation, and lowered the expression levels of relevant senescence-associated markers, such as p16 INK4a, p21 CIP1a, interleukin-6 (IL-6), and IL-8. In addition, when infected by prominent periodontal pathogens, Porphyromonas gingivalis (ATCC 33277), rapamycin-pretreated groups decreased the expression of inflammatory cytokines ( IL-6 and IL-8 ) compared with the control group. mTOR inhibition upregulated the gene expression of antioxidant components ( Cat, Sod2, and Prdx3 ; P < 0.05 ) and consequently neutralized the excessive reactive oxygen species (ROS). In conclusion, our results indicated that mTOR inhibition might rejuvenate the aging gingiva to some extent and relieve inflammation through eliminating oxidative stress.